Analisa Laporan Keuangan Syariah dalam Metode Akuntansi Akrual Basis (Studi Kasus pada PT BPRS Jabal Tsur Pandaan): Sharia Financial Statement Analysis in Accrual Basis Accounting Method (A Case Study at PT BPRS Jabal Tsur Pandaan) - Mariyah Ulfah (Fenomena, 2018)
The rapid growth of Islamic banking in East Java necessitates rigorous health assessments to ensure stability and compliance with sharia principles. This study addresses the critical issue of applying accrual-based accounting in sharia financial reporting, particularly for profit-sharing contracts. The research aims to evaluate the financial health of PT BPRS Jabal Tsur Pandaan using the CAMEL method (Capital, Assets, Management, Earnings, Liquidity). A quantitative descriptive approach was employed, involving document analysis, interviews, and questionnaires. Data were analyzed using CAMEL ratios as prescribed by Bank Indonesia. The findings reveal that PT BPRS Jabal Tsur Pandaan achieved a CAR of 13.91, BDR of 10.9, management score of 22.1, ROA of 0, BOPO of 36.8, and LDR of 2.8, resulting in a total CAMEL score of 86.51. It is concluded that the bank is classified as "healthy" (predicate 81–100). The zero ROA is attributed to the bank being only three years old, still below the 10% target. It is recommended that the bank enhance its earnings management strategies and continue strengthening its accrual-based accounting systems for more accurate period-specific revenue recognition. Pertumbuhan pesat perbankan syariah di Jawa Timur memerlukan penilaian kesehatan yang ketat untuk menjaga stabilitas dan kepatuhan syariah. Penelitian ini menyoroti isu krusial penerapan akuntansi akrual dalam laporan keuangan syariah, terutama untuk akad bagi hasil. Tujuan penelitian adalah mengevaluasi kesehatan PT BPRS Jabal Tsur Pandaan menggunakan metode CAMEL. Pendekatan deskriptif kuantitatif digunakan melalui dokumentasi, wawancara, dan kuesioner. Data dianalisis dengan rasio CAMEL sesuai ketentuan Bank Indonesia. Hasil penelitian menunjukkan PT BPRS Jabal Tsur Pandaan memperoleh CAR 13,91; BDR 10,9; manajemen 22,1; ROA 0; BOPO 36,8; dan LDR 2,8, dengan total skor CAMEL 86,51. Kesimpulannya, bank ini tergolong sehat (predikat 81–100). ROA nihil disebabkan usia bank baru tiga tahun sehingga belum mencapai target 10%. Direkomendasikan agar bank meningkatkan strategi manajemen laba dan terus memperkuat sistem akuntansi akrual untuk pengakuan pendapatan periodik yang akurat.